Width: An Indispensable Factor in Selection of Emergency Exit Door. (February 2013) - Sun, Chengyu; de Vries, Bauke
Predicting evacuees' exit-door selection is important for architects and fire engineers. Existing models used in fire prescription and evacuation simulation assume that the distance from an evacuee to an exit door is the dominant geometric factor. However, evacuation validation studies and architectural theories suggest the existence of other factors. An exit-door-selection model was built in a virtual environment covering six geometric exit-door attributes. The impacts of these attributes were surveyed quantitatively using 187 participants. The results indicate that the attribute width is an indispensable factor in the selection. It is the strongest positive factor with the feasibility to control architectural design that can compete or balance with the negative attribute distance in exit-door selection.